2010
DOI: 10.1161/hypertensionaha.109.147488
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Potassium Chloride and Potassium Bicarbonate on Endothelial Function, Cardiovascular Risk Factors, and Bone Turnover in Mild Hypertensives

Abstract: Abstract-To determine the effects of potassium supplementation on endothelial function, cardiovascular risk factors, and bone turnover and to compare potassium chloride with potassium bicarbonate, we carried out a 12-week randomized, double-blind, placebo-controlled crossover trial in 42 individuals with untreated mildly raised blood pressure. Urinary potassium was 77Ϯ16, 122Ϯ25, and 125Ϯ27 mmol/24 hours after 4 weeks on placebo, potassium chloride, and potassium bicarbonate, respectively. There were no signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
108
3
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(122 citation statements)
references
References 38 publications
(39 reference statements)
8
108
3
2
Order By: Relevance
“…This has not been evaluated in persons without CKD. However, results from studies in healthy individuals not known to have low bicarbonate suggest that oral potassium bicarbonate supplementation raises bicarbonate concentration and maintains bone health and muscle mass (41)(42)(43)(44). The results from this study suggest that raising low serum bicarbonate may improve clinical outcomes in persons with preserved eGFR.…”
Section: Discussionmentioning
confidence: 67%
“…This has not been evaluated in persons without CKD. However, results from studies in healthy individuals not known to have low bicarbonate suggest that oral potassium bicarbonate supplementation raises bicarbonate concentration and maintains bone health and muscle mass (41)(42)(43)(44). The results from this study suggest that raising low serum bicarbonate may improve clinical outcomes in persons with preserved eGFR.…”
Section: Discussionmentioning
confidence: 67%
“…The present study adds to a number of investigations, which have consistently shown a reduction in cfPWV over the short term, following different lifestyle interventions, including not only physical exercise [11][12][13][14][15][16] but also weight loss, smoking cessation and salt intake restriction [17][18][19][20][21][22][23][24][25] (Table 1).…”
mentioning
confidence: 58%
“…Intrabrachial infusion of potassium chloride potentiates NOdependent, endothelial-dependent vasodilation induced by acetylcholine in the forearm of hypertensive humans. 5 6 This effect could not be attributed to changes in natriuresis. Interestingly, in this study, potassium supplementation significantly reduced left ventricular hypertrophy and improved diastolic function, both of which are sensitive to the effect of late systolic load on the heart that occurs from wave reflections.…”
mentioning
confidence: 85%